2014
DOI: 10.7710/2162-3309.1110
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Video Abstracts in Science Journals: An Overview and Case Study

Abstract: INTRODUCTION The video abstract has emerged in recent years as a new way of communicating the results of scholarly enquiry. For library-based journal publishers who want to support multimodal scholarship, it is useful to understand the potential benefit and impact of incorporating video abstracts into their publications. This paper provides an overview of the growth of video abstracts in science scholarship, and presents a single journal case study that compares the use and potential impact of video abstracts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 8 publications
0
37
0
1
Order By: Relevance
“…Libraries should be offering expertise in description (via meta-tagging), archiving, and rights management. Libraries that host journals and have ETD programs must be encouraged to provide options for thesis video submissions (Spicer, 2014).…”
Section: Role Of Libraries In Supporting Scholarly Videosmentioning
confidence: 99%
“…Libraries should be offering expertise in description (via meta-tagging), archiving, and rights management. Libraries that host journals and have ETD programs must be encouraged to provide options for thesis video submissions (Spicer, 2014).…”
Section: Role Of Libraries In Supporting Scholarly Videosmentioning
confidence: 99%
“…1). Publishers and authors are embracing digitally based practices including social media (Darling et al 2013) and multimedia abstracts (Spicer 2014). Despite efforts to advance digitization (for a discussion, see Owen 2007;Aalbersberg et al 2014), today's scientific paper remains rooted in print traditions; a multi-page document with text and static images that is now considered by some to be "obsolete" (Somers 2018).…”
Section: Introductionmentioning
confidence: 99%
“…So far the past few years have seen growing recognition of VAs (Spicer, 2014), yet solid research is still absent except some media commentaries and passionate practice (Berkowitz, 2013; Caputo, 2015; McGrath & Brandon, 2016; Reutemann, 2018). Therefore, the study reported in this article focuses on the formal, structural aspects of VA to begin the research conversation.…”
Section: Introductionmentioning
confidence: 99%